+0  
 
0
49
4
avatar+1998 

1.

 

2.

 Jan 7, 2021
 #1
avatar+114361 
+2

1.    ∫ 3x  dx  =   3x/ ln 3  +  constant ,  (C)

 

So

 

4  =   3x / ln 3  +  C

 

4 =  31 / ln 3  +  C

 

4 - 3 / ln 3  =   C   ≈ 1.27

 

So

 

3x/ln 3  + 1.27

 

cool cool cool

 Jan 7, 2021
 #2
avatar+114361 
+2

2. 

 

∫ 3  /  sqrt ( 1  - x^2)  dx   =    3arcsin x  + C

 

2 =  3 arcsin (0)  +  C            (arcsin 0    =  0  )

 

(0, 2)

 

2  = 0  + C

 

2   = C

 

So

 

3arcsin x  +  2

 

cool cool cool

 Jan 7, 2021
 #3
avatar+1998 
+1

looks like i got the first one correct! Which is awesome!

 

The second one however, I see where i made my mistake, very simple one that i should have caught! I will take note.

 

Thank you CPhill!laugh

jjennylove  Jan 7, 2021
 #4
avatar+114361 
+1

OK......glad  to   help   !!!

 

[ My Calculus is rusty  ....LOL!!!   ]

 

 

cool cool cool

CPhill  Jan 7, 2021

17 Online Users

avatar